FEATURES OF FORMATION OF I-CONCEPT OF ADOLESCENTS (Psychology Travelogs, 2021)
The article describes the peculiarities of the formation of self-concept in adolescence and describes the factors that influence its formation. It has been found that the views of different scientists on the structure and process of forming the self-concept are significantly different, as this topic is quite broad and can be considered from different angles. However, what these approaches have in common is that an indispensable condition for the formation of the self-concept is the presence of the individual in society and active interaction with him. In addition to the features and nature of relationships in the team, important factors influencing the self-concept are the relationship with parents, pedagogical assessment, and the attitude of the child to himself.
Keywords: I-concept; adolescence; self-awareness; self-esteem; self-perception; interpersonal relationships; status in the collective